(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
The research is aimed to assess the surface and groundwater quality in Otukpo area and environs, Benue State, North Eastern Nigeria. Sixteen water samples were collected from 7 boreholes, 7 hand duck wells and 2 rivers. The water samples were analysed chemically and bacteriologically using spectrophotometric, titrimetric and membrane filtration methods. Analytical results indicated that the groundwater in the area is acidic, fresh and moderately hard. The order of abundance of the cations were in Na+<K+<Mg2+<Ca2+ while the anions were in the order of Cl-<HCO3->SO42-<NO3-. Principal Component Analysis (PCA) identified four factors that accounts for 69.73% of the total variance. Correlation analysis, Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) revealed pollution from application of agricultural fertilizers, anthropogenic contamination and rock-water interaction as the major processes responsible for the modification of surface and groundwater chemistry of the research area. The Gibbs diagram plot shows that, the sample points fall under rock dominance and weathering zones, which suggested precipitation, induced chemical weathering with the dissolution of rock-forming minerals. The piper diagram classified groundwater samples as Ca-Mg-HCO3 water type. Water Quality Index (WQI) values range from 22.05 to 56.13 which indicated good and excellent water category. The SAR values range from 0.02 to 0.66 the values belong to the excellent category and is suitable for irrigation. The overall result revealed that, the water in the research area is suitable for domestic, industrial and irrigation activities.